Manzoku - Kamaruddin, Norhamizah; Norhanuddin, Nur Widad Dayyana; Ghaffar, Adam; Ahmad Khusaini, Noryana; Musa, Norwahida (Universiti Teknologi MARA, Kedah, 2019)
Manzoku is a gamification tool used to measure satisfaction of the library patron towards services provided in the library. This is a new approach that has been applied to library environment in Malaysia to improve patron satisfaction that was adopted from business, education and human resource field. Gamifying job functions can be a great way to inspire better employee performance and improve customer satisfaction as well as staff engagement and retention (Canter, 2014). The idea behind gamification is to drive brand awareness and business goals through customer engagement. Another popular use is Gamification for learning and on boarding of new customers and introducing them to the new platforms, services, or to replace traditional tutorials (Martin, 2013). Manzoku is a research-based product produced through content analysis and observation technique to customize the game application according to the library services provided. The Sims application has been used to develop the interactive game to represent the library services virtually. The customer’s will interact with the game and give their opinions and suggestions to improve the library services while playing with the game. The game application has a potential value to be commercialized to all libraries in Malaysia as a kick start in evaluating customer’s satisfaction towards better services.